Exploring the potential of branched submicron channels-based structures in ultra-thin Ag films for SERS molecular sensing - Roa Díaz, Simón Andre; Cortés Burgos, María José; Pedano, Maria Laura (Elsevier, 2024)
Fil: Roa Díaz, Simón Andre. Consejo Nacional de Investigaciones Cientificas y Tecnicas. Oficina de Coordinacion Administrativa Ciudad Universitaria. Unidad Ejecutora Instituto de Nanociencia y Nanotecnologia. Unidad Ejecutora Instituto de Nanociencia y Nanotecnologia - Nodo Bariloche | Comision Nacional de Energia Atomica. Unidad Ejecutora Instituto de Nanociencia y Nanotecnologia. Unidad Ejecutora Instituto de Nanociencia y Nanotecnologia - Nodo Bariloche.; Argentina